Dynamic program for selecting syari’ah share for maximum profit - Maslihah, Siti; Nadhifah (Journal of Natural Sciences and Mathematics Research, 2025)
The right investment can increase a person's income by placing a number of funds in an investment instrument. One of the investment instruments is investing in the capital market by buying a number of stocks with good fundamentals. The selection of syari’ah shares is the right choice for the Indonesian people, most of whom are Muslim. The method used to select Islamic stocks in this study is dynamic programming. Simulations carried out with dynamic program algorithms produce selected syari’ah stocks, namely ACES, ICBP, SMGR and ANTM in order to get the maximum profit. Among the five shares, the one that provided the greatest return was ANTAM shares. This was proven in 2025 when ANTAM's share price rose by 22% even though the Indonesian economy was sluggish. ANTAM shares are given priority as shares that an investor must own.